Specific Aspects of Interrogation in Videoconferencing Mode (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article discusses the specific features of conducting interrogation as an investigative action via videoconferencing. Additionally, it examines the legislative gaps in this area and provides proposals and recommendations for addressing these gaps and ensuring the effective use of videoconferencing in the future.